THE DEVELOPMENT OF JONEGOROAN BATIK DESIGN WITH THE RANCAK THENGUL MOTIF USING THE WAYANG THENGUL IDEAS - Kurnia Sani, Devi; Setyawan, Setyawan (Arty: Jurnal Seni Rupa, 2021)
The development of the Jonegoroan Rancak Thengul batik motif design is carried out to produce Jonegoroan batik that is creative, innovative and opens up many economic and creative industry opportunities in Bojonegoro. This development is important considering that the Rancak Thengul motif was inspired by Bojonegoro's signature art, Wayang Thengul. The results of design development are expected to: 1) open new opportunities and perspectives on batik products with Jonegoroan Rancak Thengul motifs ranging from visual details, colors, composition, production processes to product realization. 2) Developing by combining the typical art of Wayang Thengul and the natural potential of Bojonegoro as a source of ideas by increasing the visual quality and artistic value, thus opening up market and economic opportunities in Bojonegoro. The results of this research and design development conclude that design development will be beneficial for batik industry players in Bojonegoro in developing Joegoroan batik designs. With creative and innovative developments, Jonegoroan batik will be able to open up new opportunities and make Jonegoroan batik a superior product and an economic milestone in the City of Bojonegoro.